Irreversible inhibition of cytosolic thioredoxin reductase 1 as a mechanistic basis for anticancer therapy - William C. Stafford; Xiaoxiao Peng; Maria Hägg Olofsson; Xiaonan Zhang; Diane K. Luci; Frank Leigh Lu; Qing Cheng; L. Tresaugues; Thomas S. Dexheimer; Nathan P. Coussens; Martin Augsten; Hanna-Stina Martinsson Ahlzén; et al. (2018)
Selective irreversible inhibitors of selenoprotein TXNRD1 yield anticancer efficacy without overt systemic toxicity in mouse models.